Intracellular structural modifications of natural peptidoglycan fragments preceding NOD2 signaling in mammalian cells - Shiliu Feng; Christopher Adamson; Chenyu Li; Evan Wei Long Ng; Yuan Qiao (Proceedings of the National Academy of Sciences, 2026)
Bacterial peptidoglycan fragments (PGNs) are pathogen-associated molecular patterns that activate the mammalian innate immune system, particularly through NOD2 signaling pathways. Since NOD2 is a cytosolic sensor in mammalian cells, cellular assays are commonly used to identify bioactive PGNs that elicit NOD2 response, with muramyl dipeptide (MDP) long recognized as the minimal NOD2 agonist. However, recent studies have highlighted the intracellular phosphorylation of MDP by mammalian N -acetylglucosamine kinase (NAGK) as a critical prerequisite for NOD2 activation, emphasizing the need for further investigation into other host-mediated processing of PGNs. In this study, we examined how various bacterial PGNs, differing in saccharide and stem peptide length, undergo intracellular structural modifications within mammalian cells. Our findings show that disaccharide PGNs are processed through intracellular glycosidic cleavage to generate monosaccharide MurNAc-containing PGNs intracellularly, followed by NAGK-dependent phosphorylation, uncovering an additional essential step that precedes NOD2 activation. To identify the glycosidase responsible for disaccharide PGN cleavage, we provide biochemical and cellular observations that human O -GlcNAcase functions as a promiscuous glycosidase capable of processing certain disaccharide PGNs and potentially modulate their NOD2 activation. Furthermore, we demonstrate that PGNs with a lysine-type tripeptide stem are specifically cleaved into dipeptides and that phosphorylated PGNs are subjected to dephosphorylation in mammalian cells. Together, these findings offer insights into the metabolism and intracellular processing of PGNs in mammalian cells, which are crucial in shaping the host innate immune responses.